Uncovering Critical Thinking and Mathematical Representation Skills of Pre-Service Elementary Teachers Through Cognitive Style - Achmad Salido; Sugiman Sugiman; Fery Muhamad Firdaus; Agung Prihatmojo; Agus Herwanto; Eka Yuni Andari; Widiya Saputri Wulandari; Lussy Midani Rizki (Qubahan Academic Journal)
This study examines the critical thinking and mathematical representation abilities of pre-service elementary school teachers’ students (PESTS) through the lens of field-dependent (FD) and field-independent (FI) cognitive styles. Using a qualitative descriptive approach, 39 participants completed the Group Embedded Figures Test (GEFT), problem-solving tasks, and semi-structured interviews to assess cognitive styles and representation skills. Results indicate that FD participants struggled with problem-solving, relying on prior experiences, providing superficial solutions, and using primarily symbolic and numerical representations with limited abstraction. In contrast, FI participants demonstrated more assertive critical thinking, systematically employing diverse representations including symbols, mathematical expressions, and verbal explanations to solve problems independently. These differences underscore the need for differentiated instruction, with the FD learners requiring structured support to enhance critical thinking and broaden their representation skills. The FI learners should be challenged with abstract and complex tasks to enhance their skills further. Personalized, adaptive learning strategies are essential to preparing future educators for the challenges of 21st-century teaching.